Proses Pemerolehan Bahasa Huruf Vokal Anak Tunarungu di Sekolah Luar Biasa Negeri Merangin - Julita, Ranti; Krisniawati, Ekaning; Ratnasari, Dewi; Sofyan, Agus Nero (UNIB Press, 2024)
The problem of this research is how is the language acquisition process in deaf children, especially in vowel phonemes and how is it realized. The purpose of this study is to describe how deaf children acquire vocal phonemes and explain how deaf children realize them. The subjects of this study were Alex in grade 10 at SLB Marangin and Ratna at grade 12 at SLB Marangin. The method used is descriptive analysis with a qualitative approach using observation and note taking techniques. The researcher obtained the data by listening to and recording a video that was uploaded to YouTube by Nelly entitled 'speech development assessment of deaf children in expressing vowels' which was conducted at SLB Negri Merangin. The results showed that in the pronunciation of the vowels Ratna and Alex were not clear enough in pronouncing the vowel phonemes /o/ and /i/ but the type of phonemes /o/ flanked by the phonemes /b/ and /l/ Ratna and Alex could pronounce them clearly as in the word 'ball'. Alex and Ratna also had difficulty deciphering the words 'bucket' and 'shrimp'. In the word 'ember', Ratna and Alex could not pronounce the phoneme /r/ clearly and in the word prawn, Alex and Ratna could not pronounce the consonant /ng/.